Mandatory and voluntary disclosure: a case study to the energy sector companies listed on BM&FBOVESPA - Dantas, Everton Diêgo de Moraes; Vieira, Allan Sarmento (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The aim of thisstudy was to identifyand compare thedisclosureways/tipsofsocial and environmentalinformation betweenenergy companieslisted on the BM& FBOVESPA. The disclosure of social and environmental information submitted by some energy companies listed on the BM & FBOVESPA is currently considered a factor of great importance, this because is through this information that the company shows its concern for the preservation of the environment and environmental impacts caused by them. That’s why some use the Social balance as a way of evidencing their voluntary demonstratives, such models serving to extra information to the financial statements presented by companies annually. The aforementioned work is about a research of quantitative and qualitative nature, documentary and Bibliographic, and descriptive case study, where 73 companies in the energy sector listed on the BM & FBOVESPA website have been selected to make its universe. Performed the data analysis, it was verified that of the 22 companies in the study only 5 of them disclose forms of voluntary disclosure in their sustainability reports, thereby showing the role that each one takes about social and environmental responsibility.